Clinical characteristics and management of acute generalized exanthematous pustulosis with haemodynamic instability - M. O’Brian; C. L. Carr; C. Thomas; A. R. Dominguez; M. Mauskar (Skin Health and Disease, 2021)
Abstract Background Acute generalized exanthematous pustulosis (AGEP) is a severe pustular drug eruption with rare reports of haemodynamic instability. Objective To describe the clinical characteristics, management, and outcomes of patients with AGEP‐associated haemodynamic instability. Methods This retrospective case series identified adult patients diagnosed with AGEP who had haemodynamic instability from November 2012 to February 2020 that were seen at two academic teaching hospitals with roles as a burn centre and tertiary referral centre at the University of Texas Southwestern Medical Center in Dallas, TX USA. Patients with a discharge diagnosis of AGEP that had haemodynamic instability during their eruption were included. Patients with a history of psoriasis, presentations thought to be a flare of generalized pustular psoriasis, or concurrent infection during eruption were excluded. AGEP with haemodynamic instability was characterized by degree of hypotension, dermatologic phenotype at time of dermatologic consultation, and management approach. Results This study included 19 patients with AGEP‐associated haemodynamic instability (mean age, 52 years; age range, 29–76 years; 11 (58%) female). Patients were classified on a spectrum of haemodynamic instability; three had sustained hypotension, 10 had hypotension with organ dysfunction, and six had shock. Patients with AGEP‐associated haemodynamic instability had a range of dermatologic phenotypes at initial consultation: subtle exanthematous eruption with minimal pustules, typical eruption with pustules and flexural predominance, and severe eruption with features of Stevens–Johnson syndrome. Both topical and systemic corticosteroids were used for treatment of several patients. Of the patients that required vasopressors and received systemic steroids, the majority were off vasopressors within 24 h of steroid initiation. Conclusion Approximately 22% of patients presenting with AGEP to a tertiary referral center had haemodynamic instability. Clinicians should be aware that dermatologic phenotype of AGEP at presentation does not correlate with development of haemodynamic instability.